Gen-Z Purchase Intentions Towards Electric Vehicles - Firman Messias; Maria Clara Wresti; Kurniawati Kurniawati (Dinasti Publisher, 2025)
Gen-Z, the group born between 1997-2012, has emerged as a significant market force. As this generation begins to build their careers and gain purchasing power, Gen-Z has become a crucial focus for researchers and marketers today. Their purchasing behavior differs from previous generations. Growing up with easy access to the internet and digital technology, this generation tends to spend more time online and is highly influenced by digital marketing efforts. This research aims to examine Gen-Z's purchase intentions toward electric vehicles (EVs) in the Jakarta, Bogor, Depok, Tangerang, and Bekasi (Jabodetabek) areas, mediated by the Theory of Planned Behavior (TPB). Data was collected from 335 Gen-Z respondents using Structural Equation Modeling (SEM) with AMOS. This study found that although individuals have a high level of environmental awareness, their attitudes do not always translate into actual green purchasing decisions. The research findings can help EV marketing managers develop appropriate strategies for targeting Gen-Z.